Maximal strength performance, efficiency, and myoelectric responses with differing intra-set rest intervals during paired set training. Issue 1 (January 2020) - Paz, Gabriel Andrade; de Freitas Maia, Marianna; Miranda, Humberto; de Castro, Juliana Brandão Pinto; Willardson, Jeffrey M.
Abstract: Introduction: The purpose of this study was to investigate the effect of different rest intervals within paired sets (PS) on total work and training volume, efficiency (training volume load/session duration time), and myoelectric activity. Method: Fifteen trained men participated in this study. Four experimental protocols were applied: P30 (30 s rest), P60 (60 s rest), P90 (90 s rest), and P120 (120 s rest). The PS bout consisted of a bench press (BP)/lat pull down (LPD), 30° incline bench press (BP30)/wide-grip seated row (SR), and triceps extension (TE)/biceps curl (BC) exercises. Surface electromyography (sEMG) activity of the biceps and triceps brachii were recorded. Results: Volume load (repetitions x number of exercise sets x loads) was significantly lower for the P30 (5385.8 ± 1224 kg) versus the P60 (6755.6 ± 1398.5 kg), P90 (7358.3 ± 1490.3 kg), and P120 (7463 ± 1310 kg) protocols. No significant differences in sEMG activity was noted between protocols. The efficiency (kg·min −1 ) of P30 (633.6 ± 144) was significantly higher versus P60 (397.4 ± 82.2), P90 (288.5 ± 58.4), and P120 (219.5 ± 38.5). Conclusion: Short intra-set rest intervals (60 s) within PS may be a potential alternative for increasing the volume load, since longer intra-rest (90 s and 120 s) intervals do not provide additional benefits.